Age-related Physical Performance Differences in Male Soccer Players. (1st June 2016) - Karahan, Mustafa
Abstract: The aim of this study is to identify the differences of physical performance characteristics between the amateur male adolescent soccer players in different age groups. One hundred and twenty-eight male players voluntarily participated in this study and athletes were classified in three chronological age groups as U-15, U-17 and U-19. Physical performance data showed that the U-15 group tended to be slower over 10 and 20 meters, and had the poorest agility and anaerobic power. Except for explosive power, the performance values of U-17 were lower than U-19 (p<0.05). In conclusion, there were significant differences between three groups. These agerelated differences were strongly correlated with differences in physical performance characteristics. Results suggest that anaerobic performance and sprint ability improves during maturation of amateur male adolescent soccer players. Thus, the coaches should take into consideration differences in age-related physical performance in player selection for a team or training practices.